2021
DOI: 10.3390/rs13244986
|View full text |Cite
|
Sign up to set email alerts
|

Is It All the Same? Mapping and Characterizing Deprived Urban Areas Using WorldView-3 Superspectral Imagery. A Case Study in Nairobi, Kenya

Abstract: In the past two decades, Earth observation (EO) data have been utilized for studying the spatial patterns of urban deprivation. Given the scope of many existing studies, it is still unclear how very-high-resolution EO data can help to improve our understanding of the multidimensionality of deprivation within settlements on a city-wide scale. In this work, we assumed that multiple facets of deprivation are reflected by varying morphological structures within deprived urban areas and can be captured by EO inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…The classification of DUAs typologies was performed by unsupervised k-means clustering. Similarly, both studies [48,81] identified settlements with different levels of consolidation, organization of the urban fabric, and built-up density. Note that these studies also used grids as spatial reference units.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The classification of DUAs typologies was performed by unsupervised k-means clustering. Similarly, both studies [48,81] identified settlements with different levels of consolidation, organization of the urban fabric, and built-up density. Note that these studies also used grids as spatial reference units.…”
Section: Discussionmentioning
confidence: 94%
“…In the Brazilian case, prior characterization of settlements is a mandatory step for local governments to access funding from the federal government's slum upgrading programs [4]. Furthermore, this type of characterization allows the understanding of internal structures in precarious areas to provide meaningful indicators to combat poverty through evidencebased policy-making toward more sustainable cities [81].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SLUMAP project that focused on sub-Saharan African cities investigated the potential of EO for mapping and characterising DUAs, aiming for cost efficiency. Experiments involving machine learning algorithms and satellite imagery with different spatial resolutions showed that city-level deprivation mapping could be achieved with open, cost-free Sentinel-1/2 images, while very-high-resolution images were requested to produce detailed settlement-level characterisation (Abascal et al 2022;Georganos et al 2021;Vanhuysse et al 2021). At the city scale, the (Abascal et al 2022b) location and extent of slums within a city were modelled, while detailed characteristics of the physical environment within slums were extracted at the settlement scale.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a 0.3 m resolution panchromatic sensor, an eight-band visible and near-infrared imager (operating between 397 and 1039 nanometres) with a ground sample distance (GSD) of 1.2 m, a short-wave infrared (SWIR) sensor with further eight bands (1184-2373 nm) at a resolution of 3.7 m, and finally the CAVIS (Clouds, Aerosol, Vapors, Ice, and Snow) sensor with twelve additional bands at 30 m for the retrieval of atmospheric properties [1]. These capabilities make it particularly suitable for application in urban areas, where the extremely complex morphology requires a higher level of detail [2,3].…”
Section: Introductionmentioning
confidence: 99%